Morphological lymphocytic reaction, patient prognosis and PD-1 expression after surgical resection for oesophageal cancer. Issue 10 (15th August 2019) - Baba, Y; Yagi, T; Kosumi, K; Okadome, K; Nomoto, D; Eto, K; Hiyoshi, Y; Nagai, Y; Ishimoto, T; Iwatsuki, M; Iwagami, S; Miyamoto, Y; et al.
Abstract: Background: Immune checkpoint inhibitors, such as antibody against programmed cell death protein (PD-1), have demonstrated antitumour effects in patients with malignancies, including oesophageal cancer. A lymphocytic reaction observed by pathological examination is a manifestation of the host immune response to tumour cells. It was hypothesized that a stronger lymphocytic reaction to tumours might be associated with favourable prognosis in oesophageal cancer. Methods: Using a database of resected oesophageal cancers, four morphological components of lymphocytic reactions (peritumoral, intranest, lymphoid and stromal) to tumours were evaluated in relation to clinical outcome, PD-1 expression by immunohistochemistry and total lymphocyte count in blood. Results: Resected oesophageal cancer specimens from 436 patients were included in the study. Among the four morphological components, only peritumoral reaction was associated with patient prognosis (multivariable P for trend <0·001); patients with a higher peritumoral reaction had significantly longer overall survival than those with a lower reaction (multivariable hazard ratio 0·48, 95 per cent c.i. 0·34 to 0·67). The prognostic effect of peritumoral reaction was not significantly modified by other clinical variables (all P for interaction >0·050). Peritumoral reaction was associated with total lymphocyte count in the blood ( P < 0·001), supporting the relationship between local immune response and systemic immune competence. In addition, higher morphological peritumoral reaction was associated with high PD-1 expression on lymphocytes in tumours ( P = 0·034). Conclusion: These findings should help to improve risk-adapted therapeutic strategies and help stratify patients in the future clinical setting of immunotherapy for oesophageal cancer. Graphical Abstract: Among four components of lymphocytic reactions, only peritumoral reaction was associated with patient prognosis in 436 patients with oesophageal cancer, suggesting higher peritumoral reaction as a prognostic marker. Peritumoral reaction was associated with total lymphocytes in the blood and programmed cell death protein 1 (PD-1) expression on lymphocytes in tumours. Will guide future immunotherapy